Draft Five Year Plan 1978-83 Government of India Planning Commission - Planning Commission, Government of India (Planning Commission, Government of India, 1978)
It is a cause of legitimate national pride that over this period a stagnant and dependent economy has been modernised and made more self-reliant. A modest rate of growth of per capita income has been maintained despite the growth of population. On the other hand, the numbers of unemployed and underemployed are still very high and more than 40 per cent of the population lives below the poverty line.
Government of India Planning Commission
Government of India Planning Commission